UPAYA PEREMPUAN KARIER DALAM MEWUJUDKAN KELUARGA SAKINAH (Studi Kasus Hakim Perempuan Di Pengadilan Kota Bengkulu) - Susanti, Santi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The purpose of this research  is to know the efforts of female judges in realizing happy  family. The research  was conducted in Bengkulu  City Court,  March-June 2017.  The research  method used  was survey method and  data  retrieval technique was done  by observation and  open  interview.  Data  were  analyzed  descriptively  qualitative.  The results show that there are women’s  judges to realize their family, including building effective communication, keeping  commitments to put aside  the suspicion,  willingness to give up the right to receive  income,  paying  household assistants  to do housekeep- ing, increasing  the intensity of romanticism  in the household, controlling emotions, supporting the wife’s career,  strength- ening religious knowledge  in the family, equating perception